Evaluation of Chicken Eggs Supply With Fuzzy AHP Approach Through Development of Safea Software - Agung Prayudha Hidayat; Sesar Husen Santosa; Ridwan Siskandar; Ringga Gilang Baskoro (Jurnal Logistik Indonesia, 2021)
This study aims to evaluate the supply aspect of chicken eggs. The Variables used in this research were egg stock, egg demand, and selling prices with alternatives are adding suppliers, adding customers, reducing supplier. The method of this research using Fuzzy AHp where The membership sets of fuzzy model are Triangular and Trapezodial membership function. The results of the research indicate that the main priority as a decision support for the supply of chicken egss is the selling price to customer (0,67), so that the alternative priority option is the addition of suppliers (0,75) to anticipate imbalances between the number of eggs sold and stock availability in the warehouse.